Upper circumpolar deep water influences microbial functional gene composition and diversity along the southern Central Indian Ridge and eastern Southwest Indian Ridge - Sheryl Oliveira Fernandes; Dhiraj Paul; Surya Prakash Lankalapalli; Srinivas Rao Arvapalli; Vidya PJ; John Kurian Palayil (Microbiology Spectrum)
ABSTRACT Deep sea microbial communities play a significant role in global biogeochemical processes. However, the depth-wise metabolic potential of microbial communities in hydrothermally influenced Central Indian Ridge (CIR) and Southwest Indian Ridge (SWIR) remains elusive. In this study, a comprehensive functional microarray-based approach was used to understand factors influencing the metabolic potential of microbial communities and depth-driven differences in microbial functional gene composition in CIR and SWIR. Stratified water column sampling at surface, mid, turbid/plume layer, and near bottom was done along with pertinent environmental variables at various locations along the ridges. The majority of genes (~38%–41%) throughout the water column in both regions encoded for C-cycling, particularly starch degradation indicating the predominance of heterotrophy. Genes encoding for nitrate reduction and arsenic and mercury resistance were enriched in the turbid and/or near-bottom waters, suggesting a localized influence of hydrothermally derived substrates on the metabolic potential of microbial communities. Indices for microbial functional gene diversity (H = 9.18) and evenness (J = 0.90) were highest for samples from turbid waters at SWIR. Potential temperature-salinity profiles showed the presence of nutrient-rich upper circumpolar deep water (UCDW) at >2,000 m in the study areas. Principal component analysis revealed that inorganic nutrient availability largely influenced functional gene diversity in deeper waters. The study signifies that rather than hydrothermal input, nutrients brought into the region through the UCDW could have a larger impact on metabolic processes mediated by autochthonous microbial communities and consequently have implications on deep-sea productivity.IMPORTANCELittle is known about depth-wise metabolic potential of microbial communities in hydrothermally influenced Central Indian Ridge (CIR) and Southwest Indian Ridge (SWIR) waters. In the present study, a comprehensive functional gene microarray approach was used to reveal the metabolic potential and depth-wise variation in microbial functional genes along the ridges. Up to 41% of microbial functional genes at both locations encoded for C-cycling. Availability of hydrothermally derived substrates in plumes detected along the ridges triggered an increase in the abundance of genes encoding for remediation of polycyclic aromatics, nitrate reduction, and arsenic and mercury resistance. Rather than hydrothermal input, the functional gene diversity at >2,000 m was largely influenced by inorganic nutrients transported by the nutrient-rich upper circumpolar deep water. Findings of this study are expanding the existing knowledge on new sites of hydrothermal activity along CIR and SWIR and gaining insights into ecosystem functioning in the deep sea.